2022
DOI: 10.3390/s23010383
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Imaging for Mobile Robot Navigation

Abstract: The article presents the application of a hyperspectral camera in mobile robot navigation. Hyperspectral cameras are imaging systems that can capture a wide range of electromagnetic spectra. This feature allows them to detect a broader range of colors and features than traditional cameras and to perceive the environment more accurately. Several surface types, such as mud, can be challenging to detect using an RGB camera. In our system, the hyperspectral camera is used for ground recognition (e.g., grass, bumpy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This allows reduction of the training data required for semantic classification. Classification and segmentation of hyperspectral images use Convolutional Neural Networks (CNNs), clustering, or nearestneighbor to extract spatial and spectral features [14], [15], [16]. Also, [17] shows how the existing spectral database can be used for classification, but the use of large number of classes in the database increases the computation time of the spectral similarity algorithms.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…This allows reduction of the training data required for semantic classification. Classification and segmentation of hyperspectral images use Convolutional Neural Networks (CNNs), clustering, or nearestneighbor to extract spatial and spectral features [14], [15], [16]. Also, [17] shows how the existing spectral database can be used for classification, but the use of large number of classes in the database increases the computation time of the spectral similarity algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…Our work provides a framework which can be used with an existing reference database or one can be created by the user in run-time based on the specific task or mission requirements. [18] uses hyperspectral images to annotate RGB images to train a CNN for semantic segmentation of unstructured terrains and [16] generates the spectral data for multiple semantic classes by labeling multiple pixels from each class. This makes the addition of new semantic classes cumbersome.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperspectral imaging and artificial intelligence (AI) integration have emerged as a promising avenue for non-invasive analysis and monitoring of various substances. Studies presented in [ 22 , 23 ] have demonstrated the effectiveness of AI for extracting relevant features from hyperspectral data and improving accuracy in material identification and concentration estimation.…”
Section: Introductionmentioning
confidence: 99%
“…There have been multiple efforts to develop vehicle-mounted hyperspectral cameras to collect datacubes off-road [96,97] and on-road [98,99,92]. In particular, all the examples mentioned above make use of VNIR cameras, which are well-suited to detect vegetative properties, but do not have the same insight into the numerous absorption bands in the SWIR spectrum [55].…”
Section: Hyperspectral Terrain Datasetsmentioning
confidence: 99%